2002
DOI: 10.1046/j.1440-1827.2002.01340.x
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma arising from a seminal vesicular cyst: Possible relationship between chronic inflammation and tumor development

Abstract: A case of squamous cell carcinoma arising within an acquired seminal vesicular cyst is described. A 61-year-old man was hospitalized because of hemospermia and dysuria. Under the diagnosis of a left seminal vesicular cyst, surgical resection was performed. Pathological examination revealed squamous cell carcinoma within a seminal vesicular cyst, along with squamous metaplastic foci and severe chronic inflammation. Cell proliferation, determined with reference to MIB-1 labeling indices, showed a stepwise increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…LPS-induced TLR4 signaling pathways showed that TLR4, CD14 and Myd88 complexes were the indispensable components to recognize LPS [9,10,11,12]. Additionally, it has demonstrated that LPS treatment not only affected immune cells such as T cells and macrophage, but also had an impact on many types of epithelial cells through TLR4 signaling, which led to local infections or inflammatory processes [13]. Intestinal epithelial cells (IECs) play an active role in the mucosal immune response to pathogenic bacteria, which mediate the non-specific acute inflammatory response [14].…”
Section: Introductionmentioning
confidence: 99%
“…LPS-induced TLR4 signaling pathways showed that TLR4, CD14 and Myd88 complexes were the indispensable components to recognize LPS [9,10,11,12]. Additionally, it has demonstrated that LPS treatment not only affected immune cells such as T cells and macrophage, but also had an impact on many types of epithelial cells through TLR4 signaling, which led to local infections or inflammatory processes [13]. Intestinal epithelial cells (IECs) play an active role in the mucosal immune response to pathogenic bacteria, which mediate the non-specific acute inflammatory response [14].…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged chronic inflammation induced DNA damage and the induction of squamous metaplastic changes may play an important role during the pathogenesis of SCC. [3]…”
Section: Discussionmentioning
confidence: 99%
“…To date, no more than 5 cases of primary SCC arising from the seminal vesicle have been reported. [37] Through reviewing the literature, we summarized these cases between 2002 and 2016 (Table 1). Patient age at the time of diagnosis ranged from 26 to 69 years, with a mean age at 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, the seminal vesicles are composed of an external fibrous connective tissue layer, a middle smooth muscle layer and an inner mucosal layer (6). The squamous cell tumor in the seminal vesicle may be due to chronic inflammatory stimulation-induced squamous metaplasia and subsequent malignant transformation (7). Primary SCC of the seminal vesicle is extremely rare, with only two cases reported in the English literature to date (1,2).…”
Section: Discussionmentioning
confidence: 99%